2009
DOI: 10.1111/j.1445-5994.2008.01879.x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of early bereavement on psychological and behavioural cardiac risk factors

Abstract: These results offer insight into the psychological, behavioural and physical changes that may contribute to cardiovascular risk in bereavement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
50
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 59 publications
(110 reference statements)
3
50
1
1
Order By: Relevance
“…Previous research has shown that related emotional stressors, such as anger, 16, 17 anxiety 16 and depression 18 may trigger cardiovascular events in the following hour(s). 19, 20 For instance, in our study population, 16 39 of the 1623 (2.4%) patients recruited by 1995 reported an episode of anger in the 2 hours prior to MI onset, resulting in a 2.3-fold (95%CI 1.7 to 3.2) increased risk of MI; there was a 1.6-fold (95% CI 1.1 to 2.2) elevated risk of MI in the 2 hours following episodes of marked anxiety. In a study of 295 patients interviewed immediately following an acute coronary event, 18 46 (18.2%) reported a time-limited episode of depression in the 2 hours before symptom onset.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research has shown that related emotional stressors, such as anger, 16, 17 anxiety 16 and depression 18 may trigger cardiovascular events in the following hour(s). 19, 20 For instance, in our study population, 16 39 of the 1623 (2.4%) patients recruited by 1995 reported an episode of anger in the 2 hours prior to MI onset, resulting in a 2.3-fold (95%CI 1.7 to 3.2) increased risk of MI; there was a 1.6-fold (95% CI 1.1 to 2.2) elevated risk of MI in the 2 hours following episodes of marked anxiety. In a study of 295 patients interviewed immediately following an acute coronary event, 18 46 (18.2%) reported a time-limited episode of depression in the 2 hours before symptom onset.…”
Section: Discussionmentioning
confidence: 99%
“…21, 22 Acute bereavement is associated with psychological, behavioral and physiologic sequelae. 2022 In particular, bereavement is associated with higher levels of negative affect, including symptoms of depression, anxiety and anger. 20 Acute bereavement is also associated with reduced sleep time, reduced appetite, lower total cholesterol and low density lipoprotein and higher cortisol levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to affecting well-being (Buckley et al, 2009), this stressor has also been linked to risk for dementia. For instance, studies have found parental death during childhood (Persson and Skoog, 1996) and maternal death during adolescence (Norton et al, 2011) to be associated with six-fold and two-fold increased risk for dementia and AD, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…(3,4) Even though the mortality of bereavement has been described in several populations, the role of modifying factors after bereavement such as incident cardiovascular disease (CVD) and depressive symptoms are not well understood. (3) Bereavement increases the risk for cardiovascular events (5) and depressive symptoms (6). Each of these factors—bereavement, (14) CVD, (7) and depression (7) – have been independently linked to mortality, but they have not been examined together in a single study.…”
mentioning
confidence: 99%